Problem ochrony interesu właściciela nieruchomości przy ustanawianiu służebności przesyłu - Kursa, Sławomir Patrycjusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article includes an evaluation of the legal protection of the interest of the property owner in establishing the servitude of the transmission according to the binding regulations and in the draft amendments to the servitude of transmission. Considers the issue of determining an “adequate remuneration” for establishing the servitude of transmission. The author presents a proposal de lege ferenda in the form of a proposal for a blanket regulation under which the competent minister would determine by regulation the width of the zone necessary for the transmission company to exercise its entitlements, taking into account the types, specifics and parameters of transmission devices, which would lead to the unification of practice in this regard.